ZAKAT POTENTIAL MANAGEMENT STRATEGY IN INDONESIA - Maghfirah, Maghfirah (IAIN Tulungagung, 2021)
Management of Zakat has a great potential to fail to optimize the potential of Islamic philanthropy which is significant in tackling poverty and improving the welfare of the people. This article will analyze the effectiveness of zakat management in the modern economy. This research uses an empirical or sociological juridical approach and is analytically descriptive. Data collection methods in this research using documentation. Whereas the method of data analysis, carried out qualitatively juridical. The results of the research are the requirements for the fffectiveness of receiving zakat funds at Badan Amil Zakat Nasional; (1) Establish the concept of expansion in zakat obligations, (2) Management of zakat from fixed assets and non-permanent assets, (3) Accountable and professionally managed administration, (4) An accountable distribution; prioritizing domestic distribution, fair distribution, build trust between Muzakkī and Mustaḥiq zakat, (5) Job productivity through Islamic management and (6) Zakat distribution model in modern economy; distribution of zakat for poverty due to unemployment (a compulsion) and distribution of zakat for poverty due to unemployment of Khiyāriyah (an option).